The Norton anthology of poetry - Ferguson, Margaret (W. W. Norton, 1996)
The fourth edition of this standard work contains 1800 poems by 300 poets, with 600 poems and 100 poets newly included. The anthology offers more poetry by women (40 new poets), with special attention to early women poets. The book also includes a greater diversity of American poetry, with double the number of poems by African American, Hispanic, native American and Asian American poets. There are 26 new poets representing the Commonwealth literature tradition: now included are more than 37 poets from Australia, New Zealand, Ireland, Scotland, Wales, the Caribbean, South Africa and India. A reconsideration of many classic poets, from Shakespeare and Bradstreet to Larkin and Rich has been added in this edition, together with a wider representation of the beginnings of poetry in English: the Anglo-Saxon "Caedmon's Hymn" and selections from "Beowulf", as well as Middle English lyrics, popular riddles, romance, allegory, and the verse tales of Chaucer and Langland, are now included. The collection also includes short biographical sketches and a system of annotation.